Controlled removal of fluoride by ZIF-8, ZIF-67, and Ni-MOF of different morphologies - Amir Afarinandeh; Kambiz Heidari; Mariusz Barczak; Magda H. Abdellattif; Zahra Izadi Yazdanaabadi; Ali Akbar Mohammadi; Gholam Ali Haghighat; Mahmoud Shams (Arabian Journal of Chemistry, 2023)
As an emerging class of nanoporous materials, Metal Organic Framework (MOFs) are distinguished for environmental remediation. ZIFs and Ni-MOF chosen as fluoride (F-) scavengers due to their robust structures and straightforward synthesis routes. F- adsorption was studied as a function of the ZIFs geometry and structural properties. The efficacy of MOFs for F- abatement was in the order of ZIF-67-NO3 (70.1%) > ZIF-8-Cube (64.7%) > ZIF-67-OAc (62.4%) > ZIF-8-Cuboid (59.2) > Ni-MOF (58.5%) > ZIF-8-Octahedron (57.1%) > ZIF-8-Leaf (55.3%) > ZIF-67-SO4 (55.1%) > and ZIF-67-Cl (52.3%). The key operating variables i.e. pH, mixing time, F- concentration, and ZIF-67-NO3 dose were modeled using the Box-Behnken design (BBD). The model revealed the process mainly influenced by solution pH. The model optimized the operating condition and obtained a maximum 85.9% F- removal by mixing time = 41.1 min, ZIF-67-NO3 dose = 0.9 g/L, solution pH = 4.86, and F- = 6.5 mg/L. Non-linear form of isotherm and kinetic models disclosed the multilayers F- adsorption onto ZIF-67-NO3 with an qmax =25.9 mg/g, and chemisorption as the rate-controlling step. F- sorption decreased slightly by temperature in the range of 303 to 323 K. The structure of ZIF-67-NO3 remained stable under three consecutive use-reuse cycles with an about 10% loss in removal efficiency.